NLRP3 Inflammasome in Vascular Disease: A Recurrent Villain to Combat Pharmacologically - Ainara González-Moro; Inés Valencia; Licia Shamoon; Carlos Félix Sánchez-Ferrer; Concepción Peiró; Fernando de la Cuesta (Antioxidants, 2022)
Despite the great advances in medicine, mortality from cardiovascular diseases keeps on growing. This tendency is not likely to change considering the pandemic proportions of obesity and diabetes. Besides, the global population is more aged as life expectancy increases, and vascular aging plays a key role in the increased risk of vascular disease. In light of recent trials, namely the CANTOS study, showing the enormous potential of anti-inflammatory therapies and in particular those targeted to IL-1β, a change in therapeutical management of cardiovascular diseases is coming about. The NLRP3 inflammasome is a multiprotein complex that assembles to engage the innate immune defense by processing the maturation of pro-inflammatory cytokines IL-1β and IL-18. Substantial evidence has positioned the NLRP3 inflammasome at the center of vascular disease progression, with a particular significance in the context of aging and the low-grade chronic inflammation associated (inflammaging). Therefore, pharmacological blockade of the NLRP3 inflammasome and its end products has arisen as an extremely promising tool to battle vascular disease. In this review, we discuss the mechanisms by which the NLRP3 inflammasome contributes to vascular disease, with particular attention to the consequences of aging, and we enumerate the therapeutic options available to combat this recurrent villain.